Optimal Investment of the Unconfined Aquifer Adjacent to the Syrian Coast, which Occupies the Coastal (plain) Area between the AL-Sin and AL-Ross Rivers (Syria) - Hayek, Sharif; ALasaad, Ali; Mohammad, Dimah (Latakia University Journal -Engineering Sciences Series, 2019)
The demand for fresh water in coastal areas is increasing because of increased economic activity. The Syrian coast faces this problem, and it is necessary to solve it in an appropriate scientific manner. The research area is located in the Syrian coast between the Sin and Rous river. It has an area of 72 km2. The aim of the research is to assess the behavior of the aquifer system in the area of water exchange with sea water. After the construction of a numerical model of the freshwater layer - the sea using MODFLOW code within the GMS program. After calibration, the scenario of water resources without sea water intrusion was the scenario of drilling 4 groups of wells each group includes 5 wells, with an average of 50-300 m3/day, which led to an increase in the flow of wells in the region to about 17800 m3/day. يزداد الطلب على المياه العذبة في المناطق الساحلية بسبب زيادة النشاط الاقتصادي، مما يستدعي زيادة ضخ المياه الجوفية العذبة لتلبية تلك الاحتياجات، وهذا يسبب هبوط مناسيب المياه الجوفية وخللاً في التوازن الهيدروديناميكي بين المياه الجوفية العذبة ومياه البحر. ويواجه الساحل السوري هذه المشكلة، ومن الضروري حلها بأسلوب علمي مناسب. تقع المنطقة المدروسة في الساحل السوري بين نهري السن والروس، يحدها البحر المتوسط من الغرب، وطريق عام اللاذقية – طرطوس من الشرق. وتبلغ مساحتها 72 كم2. يهدف البحث إلى تقييم سلوك نظام طبقة المياه الجوفية الحرة في منطقة التبادل المائي بينها وبين مياه البحر. وبعد بناء نموذج عددي لطبقة المياه العذبة – البحر باستخدام كود MODFLOW ضمن برنامج GMS، وبعد معايرته تم اقتراح سيناريو لاستثمار الموارد المائية في منطقة البحث دون حدوث التداخل بين مياه البحر والمياه العذبة من خلال سيناريو حفر 4 مجموعات آبار، تضم كل منها 5 آبار، إضافة إلى آبار الأهالي بتصريف 50-300 m3/day، مما أدى إلى زيادة تدفق الآبار في المنطقة إلى حوالى 17800 m3/day.